2014
DOI: 10.1371/journal.pone.0109473
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Intracranial Hemorrhage Correlates with Preinjury Brain Atrophy, but Not with Antithrombotic Agent Use: A Retrospective Study

Abstract: BackgroundThe impact of antithrombotic agents (warfarin, clopidogrel, ASA) on traumatic brain injury outcomes is highly controversial. Although cerebral atrophy is speculated as a risk for acute intracranial hemorrhage, there is no objective literature evidence.Materials and MethodsThis is a retrospective, consecutive investigation of patients with signs of external head trauma and age ≥60 years. Outcomes were correlated with antithrombotic-agent status, coagulation test results, admission neurologic function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 48 publications
3
32
1
Order By: Relevance
“…This latter effect has been considered to be mediated by nuclear factor kappa B (NF-κB) [264]. Although there is a potential risk of bleeding complications in a TBI situation when using ASA [265], the results of two studies showed no hazardous effects of ASA intake prior to injury [266,267].…”
Section: Acetylsalicylic Acid (Asa)mentioning
confidence: 99%
“…This latter effect has been considered to be mediated by nuclear factor kappa B (NF-κB) [264]. Although there is a potential risk of bleeding complications in a TBI situation when using ASA [265], the results of two studies showed no hazardous effects of ASA intake prior to injury [266,267].…”
Section: Acetylsalicylic Acid (Asa)mentioning
confidence: 99%
“…In the future, we plan extend the proposed approach to segment lesions as well as CSF using a single DRINet. This is useful in clinical settings for prognostication after stroke [44] or estimating cerebral haemorrhage risk [45], [46].…”
Section: Discussionmentioning
confidence: 99%
“…By virtue of their common cortical atrophy and high use of antiplatelet/anticoagulant medications, older persons are at higher risk of intracranial injury despite normal GCS . While the incidence of traumatic intracranial bleeds is extensively researched for warfarin, new oral anticoagulation (NOAC) therapies include direct thrombin (dabigatran) or Factor Xa (rivaroxaban and apixaban) inhibitors .…”
Section: Scenario 2: Motor Vehicle Accidents – Assessing Beyond the Amentioning
confidence: 99%